Application of tuned viscous mass damper isolation systems for equipment-induced vibration control of industrial buildings. (May 2023) - Zhu, Zhengrong; Zhou, Yun; Tan, Zhongkun; He, Hui; Zhou, Xiaofeng
Abstract: Tuned viscous mass dampers (TVMDs) are promising inerter-based devices for vibration control of civil structures. Previous studies chiefly focused on the vibration control performance of TVMDs for a main structure subjected to seismic excitations. In this study, the application of TVMD isolation systems for equipment-induced vibration control of industrial buildings is explored. A closed-form solution for optimum design parameters of TVMD isolation systems is proposed based on the fixed-point theory. The design procedure of TVMD isolation systems is provided to balance the vibrations of the main structure and equipment. The validation of TVMD isolation systems is conducted based on a real industrial building. The numerical analysis results show that TVMD isolation systems optimally designed using the proposed closed-form solution are highly effective in controlling the acceleration and displacement responses of both the main structure and equipment. Moreover, the results confirm that TVMD isolation systems can be used as an effective control strategy to solve the comfort problem of industrial buildings induced by rotary mechanical equipment. This is because the inner degree of freedom in a TVMD is amplified when the TVMD is tuned to resonate with the main structure, which provides a significantly improved energy-dissipation ability of the TVMD isolation system.